Offshore wind a comprehensive guide to successful offshore wind farm installation - Thomsen, Kurt E. (Academic Press, 2014)
Annotation Offshore Wind is the first-ever roadmap to successful offshore wind installation. It provides a ready reference for wind project managers, teaching them how to deal with complications on-site, as well as for financers, who can utilize the text as an easy guide to asking the pivotal questions of petitioning wind project developers. These developers' planning stages will be improved by the book's expert advice on how to avoid wasting money by scoping out and mitigating potential problems up-front. Wind turbine manufacturers will benefit from insights into design optimization to support cheaper installation and hauling, thereby incurring lower project costs, and helping developers establish a quicker route to profitability. The book sheds light not just on how to solve a particular installation difficulty, but delves into why the problem may best be solved in that way. Enables all stakeholders to realize cheaper, faster, and safer offshore wind projectsExplains the different approaches to executing on- and offshore projects, highlighting theeconomic impacts of the various financial and operational choicesProvides practical, proven advice on how tough challenges can be overcome,using real-life examples from the author's experiences to illustrate key issues.
Includes index.
Keywords: Offshore wind power plants.; elektronické knihy; electronic books